Cell therapy for scleroderma: progress in mesenchymal stem cells and CAR-T treatment - Liting Chen; Rongshan Huang; Chaoshuo Huang; Guiming Nong; Yuanyuan Mo; Lvyin Ye; Kunhong Lin; Anping Chen; Anping Chen (Frontiers in Medicine)
Cell therapy is an emerging strategy for precision treatment of scleroderma. This review systematically summarizes the research progress of mesenchymal stem cell (MSC) and chimeric antigen receptor T cell (CAR-T) therapies in scleroderma and discusses the challenges and future directions for development. MSCs possess multiple functions, including immunomodulation, anti-fibrosis, and promotion of vascular regeneration, all of which can improve multiple pathological processes associated with scleroderma. Studies have demonstrated that MSCs can alleviate skin fibrosis by inhibiting CCL2 production and reducing the recruitment of pathological macrophages; their paracrine effects can exert extensive regulatory functions. CAR-T cell therapy ca specifically target and eliminate autoreactive immune cells, exhibiting enhanced specificity and personalized potential. Different cell therapies may have complementary and synergistic effects in treating scleroderma, such as MSCs exerting their effects through paracrine mechanisms while CAR-T cells specifically eliminate pathological cells. Furthermore, cell-free therapies derived from MSCs, such as extracellular vesicles or exosomes, may help circumvent the limitations of MSC therapy. Although cell therapy has opened new avenues for the precision treatment of scleroderma, it still faces numerous challenges. In the future, it is essential to strengthen integration of basic and clinical research, establish standardized protocols for cell preparation and quality control, develop personalized treatment plans, and rationally combine cell therapy with existing treatment methods to maximize its advantages and improve patient prognosis and quality of life.